Satisfaction Score among Women Undergoing Vaginal Delivery after Cesarean Delivery in A Tertiary Referral Hospital in Jordan - Basha, Asma; Alkhatib, Yasmine; khrais, Mai; wahba, Samah; Obeidat, Ala’eddien; Alryalat, Saif Aldeen (Jordan Medical Journal, 2025)
Background: Cesarean section (CS) is a prevalent surgical procedure in Jordan, and its incidence has been on the rise. While it has several benefits, many women report lower satisfaction with CS. This study aimed to assess maternal satisfaction level with vaginal birth after cesarean section (VBAC) in a tertiary referral hospital in Jordan. Methods: The descriptive study was conducted at Jordan University Hospital in 2021-2022. A total 100 women with alive singleton pregnancy with no severe extragenital diseases, pregnancy complications or congenital abnormalities who underwent VBAC were enrolled the study. Women with multiple gestation, congenital fetal anomalies, intrauterine fetal death, severe extragenital pathology, and pregnancy complications were excluded. Participants’ satisfaction levels were gauged using a four-point scale. Results: The level of satisfaction with occurred 94%. The primary reasons cited for choosing VBAC was faster recovery ;45% and less pain ;28,0%. Conclusion: Most women in the study expressed high satisfaction with their VBAC experience, emphasizing the importance of physician-led counseling and the potential benefits of VBAC over repeat CS. Further research is needed to understand factors affecting satisfaction and how to enhance maternal experience with childbirthing.